1992
DOI: 10.3354/meps083273
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of viruses into the budget of microbial C-transfer A first approach

Abstract: Viral lysis of bacteria has been suggested to be a quantitatively important process in the removal of bacteria, and potentially also in the production of DOC, in the ocean. In order to investigate the quantitative role of viruses in the pelagic microbial ecosystem, a die1 study was undertaken, comprising measurements of particulate and dissolved primary production, bactenal production, bacterial grazing by flagellates, bacterial lysis by viruses, and production of viruses. Estimates of algal excretion (4.7 pm0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
158
5

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(170 citation statements)
references
References 6 publications
7
158
5
Order By: Relevance
“…VP estimates over a depth gradient in the hyper-eutrophic and stratified freshwater lake Plußsee ranged from 0.2 × 10 10 to 1.9 × 10 10 viruses l -1 d -1 using the FVIC method (Weinbauer & Höfle 1998b). VP estimates based on measurements of viral decay ranged from 7 × 10 10 to 155 × 10 10 viruses l -1 d -1 in coastal Norwegian waters (Heldal & Bratbak 1991) and 17 × 10 10 viruses l -1 d -1 in the Bay of Århus, Denmark (Bratbak et al 1992). However, as the aggregate results of this study demonstrate, a meaningful comparison of reported VP rates between different marine environments is complicated by the inherent variability between methods.…”
Section: Methods Evaluationmentioning
confidence: 77%
See 2 more Smart Citations
“…VP estimates over a depth gradient in the hyper-eutrophic and stratified freshwater lake Plußsee ranged from 0.2 × 10 10 to 1.9 × 10 10 viruses l -1 d -1 using the FVIC method (Weinbauer & Höfle 1998b). VP estimates based on measurements of viral decay ranged from 7 × 10 10 to 155 × 10 10 viruses l -1 d -1 in coastal Norwegian waters (Heldal & Bratbak 1991) and 17 × 10 10 viruses l -1 d -1 in the Bay of Århus, Denmark (Bratbak et al 1992). However, as the aggregate results of this study demonstrate, a meaningful comparison of reported VP rates between different marine environments is complicated by the inherent variability between methods.…”
Section: Methods Evaluationmentioning
confidence: 77%
“…In low productivity environments most BP is lost to grazing, while in more productive coastal and estuarine environments BP typically exceeds grazing (Strom 2000). Making a conclusion for the impact of viral lysis on BP across a range of aquatic environments is confounded by the inexplicable observation that viral lysis often consumes >100% of BP (Bratbak et al 1992, GuixaBoixereu et al 2002. For the VP rates reported here, 6 of the 14 FLV-based estimates showed >100% of BP consumed.…”
Section: Thymidine Incorporationmentioning
confidence: 99%
See 1 more Smart Citation
“…Viral lysis of bacteria has been thought to create a close loop in which bacterial carbon is cycled back to the bacterial population or respired, and nutrients are regenerated (Proctor and Fuhrman, 1991;Bratbak et al, 1992;Thingstad et al, 1993). Consequently, bacterial lysis diverts carbon and other biologically elements away from higher trophic levels or may simply delay their transportation toward them (Fuhrman, 1992), by keeping the dissolved nutrients within the so-called "viral loop" (Suttle and Chan, 1993).…”
Section: The Viral Loopmentioning
confidence: 99%
“…Typically, bacterial abundance in the ocean is of the order of 10 6 -10 7 individuals/ml, and the relative abundance of viruses, bacteria, and heterotrophic nanoflagellates [(HNF), the dominant group of protozoan predators of bacteria] is 10:1:10 -3 (Noble and Fuhrman 1998;Tanaka and Rassoulzadegan 2002). This implies that frequent interactions occur between organic and inorganic substrates, bacteria, viruses, and protozoan predators, which act as strong trophic links connecting phytoplankton-derived organic resources to the higher trophic levels via heterotrophic bacteria, and form the basis for the important biogeochemical roles played by microbial food webs in aquatic systems (referred to as the microbial loop by Azam et al 1983, and the viral loop by Bratbak et al 1992). In addition, viral lysis and protozoan predation are two major sources of bacterial mortality (Fuhrman and Noble 1995;Fuhrman 1999;Strom 2000;Wommack and Colwell 2000), although their relative contribution to bacterial mortality may vary greatly among and within ecosystems (Weinbauer and Höfle 1998;Colombet et al 2006;Lymer et al 2008) or seasons (Jacquet et al 2005;Pradeep Ram et al 2005).…”
Section: Introductionmentioning
confidence: 99%